1984
DOI: 10.1007/bf02409657
|View full text |Cite
|
Sign up to set email alerts
|

A reevaluation of stimulus overselectivity: Restricted stimulus control or stimulus control hierarchies

Abstract: Stimulus overselectivity, previously described as restricted stimulus control, was examined in preschool children. Twenty-seven subjects, after being trained to respond to a two-component auditory stimulus (S+) and not to respond to a different two-component auditory stimulus (S-), were tested to determine which stimulus elements of the complexes exerted control. Subjects that met the operational definition of overselectivity were found to have exhibited a hierarchy of stimulus control. What differentiated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

1985
1985
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
2
17
0
2
Order By: Relevance
“…Overselectivity has also been reported in typical preschoolers (Bickel et al 1984) and older children (Eimas 1969;Koegel and Wilhelm 1973), in learning disabled children (Bailey 1981), in hearing-impaired children (Fairbank et al 1986), in mentally retarded children (Brack 2001;Huguenin 1997) and mentally retarded youth without autism (Dickson et al 2006;Dube and McIlvane 1997;Huguenin 1997;Schneider and Salzberg 1982), and in adults with autism (Matthews et al 2001;Remington et al 2009). Clearly, stimulus overselectivity is not unique to autism (Dube et al 2003;McHugh and Reed 2007;Miyashita 1981), but it is a phenomenon common in autism as a slew of mostly older studies reveals (Anderson and Rincover 1982;Bickel et al 1984;Boser et al 2002;Chiang and Carter 2008;Dunlap et al 1979;Edwards et al 1976;Falcomata et al 2007;Frankel et al 1984;Gersten 1983;Glenn et al 1980;Hedbring and Newsom 1985;Katoh and Kobayashi 1985;Koegel and Wilhelm 1973;Koegel and Rincover 1976;Koegel and Schreibman 1977;Koegel et al 1979;Kolko et al 1980;Kovattana and Kraemer 1974;Matthews et al 2001;Myles et al 1989;Ploog and Kim 2007;…”
Section: Prevalence Of Stimulus Overselectivitymentioning
confidence: 88%
See 1 more Smart Citation
“…Overselectivity has also been reported in typical preschoolers (Bickel et al 1984) and older children (Eimas 1969;Koegel and Wilhelm 1973), in learning disabled children (Bailey 1981), in hearing-impaired children (Fairbank et al 1986), in mentally retarded children (Brack 2001;Huguenin 1997) and mentally retarded youth without autism (Dickson et al 2006;Dube and McIlvane 1997;Huguenin 1997;Schneider and Salzberg 1982), and in adults with autism (Matthews et al 2001;Remington et al 2009). Clearly, stimulus overselectivity is not unique to autism (Dube et al 2003;McHugh and Reed 2007;Miyashita 1981), but it is a phenomenon common in autism as a slew of mostly older studies reveals (Anderson and Rincover 1982;Bickel et al 1984;Boser et al 2002;Chiang and Carter 2008;Dunlap et al 1979;Edwards et al 1976;Falcomata et al 2007;Frankel et al 1984;Gersten 1983;Glenn et al 1980;Hedbring and Newsom 1985;Katoh and Kobayashi 1985;Koegel and Wilhelm 1973;Koegel and Rincover 1976;Koegel and Schreibman 1977;Koegel et al 1979;Kolko et al 1980;Kovattana and Kraemer 1974;Matthews et al 2001;Myles et al 1989;Ploog and Kim 2007;…”
Section: Prevalence Of Stimulus Overselectivitymentioning
confidence: 88%
“…For example, Bickel et al (1984) showed overselectivity in typical preschoolers, and McHugh and Reed (2007) found an increased tendency to be overselective in their elderly group of typical adults when distracters were used. Eimas (1969) studied Kindergarteners through FourthGraders and reported more overselectivity for the younger children.…”
Section: Chronological Agementioning
confidence: 96%
“…1997) e em crianças expostas ao ensino formal da leitura, mas que não aprenderam a ler (Cardoso & Kato, 2005;de Rose & cols, 1989;de Sena, Kato & Cruz, 2005;de Souza & cols, 1999;Melchiori & cols., 1992;Nascimento & cols., 2004). Sua ocorrência tem sido demonstrada quando apenas um aspecto do estímulo complexo é "atentado" pelo indivíduo (Bickel, Richmond, Bell & Brown, 1986;Bickel, Stella & Etzel, 1984;Meisel, 1981). O controle restrito de estímulos tem sido amplamente documentado em pessoas com necessidades educacionais especiais (Bickel & cols., 1984;Bickel & cols., 1986;Lovaas & cols., 1979;Meisel, 1981;Wilhelm & Lovaas, 1976), limitando a aquisição de novos comportamentos.…”
Section: K R S Alves E Colsunclassified
“…Laboratory investigations have been conducted to assess autistic children's limitations in responding to complex multicomponent structured stimuli (e.g., Alien & Fuqua, 1985;Bickel, Stella, & Etzel, 1984;Frankel, Simmons, Fichter, & Freeman, 1984;Koegel, Burke, Kennedy, & Lanahan, 1987;Kovattana & Kraemer, 1974;Nelson, Gergenti, & Hollander, 1980;Reynolds, Newsom, & Lovaas, 1974;Schreibman, Kohleberg, & Britten, 1986) as well as complex multicomponent social stimuli (e.g., Schreibman & Lovaas, 1973). The results obtained from these studies indicate that when autistic children are presented with a complex stimulus, they commonly respond to a limited number of components contained within the stimulus.…”
Section: Introductionmentioning
confidence: 99%